A COMPARATIVE SCREENING AND EVALUATION OF THE TOTAL PHENOLICS, FLAVONOIDS, AND ANTIOXIDANT PROPERTIES IN THE SEED EXTRACTS OF PUNICA GRANATUM L., PSIDIUM GUAJAVA L., AND VITIS VINIFERA L. - S NELSON, SAMBA; ALAGAR YADAV, SANGILIMUTHU (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The synthetic antioxidants produce numerous adverse effects to overcome these adverse effects and the use of natural products is the alternative. In this study, the evaluation of total phenolics, flavonoid contents, and antioxidant properties of Punica granatum, Psidium guajava, and Vitis vinifera seed extracts was done. Methods: The total phenolic content was estimated with gallic acid equivalent and the total flavonoid contents were estimated on quercetin equivalent. For the antioxidant properties of selected seed extracts, the 2,2-diphenyl-1-picrylhydrazyl radical scavenging, ferrous reducing power, and hydrogen peroxide radical scavenging assays were followed to find the free radical scavenging ability of the selected seed extracts. Results: The ethyl acetate extract of P. granatum seed contains higher phenolic content (70.25±1.25 μg/ml) and flavonoid content (58.15±1.85 μg/ml) and possesses a high free radical scavenging ability. Based on the inhibitory effects of fruit seeds against synthetic radicals, they can be ranked as P. granatum>P. guajava>V. vinifera. Conclusion: According to overall observations of the study, the pomegranate seed extract contains a higher level of phenolic and flavonoid contents and shows a higher scavenging effect against free radicals among the others seeds. Phytochemical screening showed that the ethyl acetate extract of pomegranate fruit seed possesses more secondary metabolites compared to other seed extracts.